PROBLEMATIKA PEMBERDAYAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI SEKOLAH MENENGAH PERTAMA NEGERI 11 JAKARTA SELATAN - Baroroh, Fatimatul; Rahmah, Alifia Taufika; Mauludi, Rafid; Arief, Armai; Asy'ari, Hasyim (Hijri, 2023)
Human resources have an important role in an organization, without human resources the organization will not run. Because human resources can control capital, technology and money. Studying the science of human resources cannot be separated from other management activities or processes such as strategic planning, management balancing, and organizational development. The relationship between these aspects of management is so close that it is difficult to separate one from the other. The potential of human resources needs to be developed through the process of human resource development in order to realize human resources that have the ability and skills or quality human resources in accordance with the nature and objectives of national development in Indonesia. This can be done through training and development. Human resource development is very necessary because it has an important aspect in increasing the productivity of human resources and also has certain objectives. The purpose of this study is to describe the problematics of empowerment and human resource development in public junior high school 11 South Jakarta. This research was conducted with a descriptive qualitative approach. The subjects of this research are teachers, principals and deputy heads of student affairs. Data collection techniques are interviews and observations. Furthermore, it is used as material in carrying out focus group discussions (FGD). Data analysis is done through three steps, namely: data reduction; data display; and conclusion drawing/verifying. The results showed that the school's problems in empowering human resources in this case teachers at SMPN 11 showed that the lack of motivation, lack of discipline, and lack of ownership of the teachers concerned. School problems in empowering TAS (School Administrative Personnel) at SMPN 11 are: the position of head of school administration personnel at SMPN 11 South Jakarta has not been filled.